Modeling of small Band-gap CNT for designing of faster switching CNTFET - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz; Motakabber, S. M. A. (2013)
This paper suggests the modeling phenomena of small band-gap Carbon Nanotube (CNT). Device physics of CNT is studied and do the calculation of sub-band for zigzag CNT to model small band-gap tubes. Each carbon nanotube is described as a graphene sheet rolled into a cylindrical shape so that the structure is one dimensional with axial symmetry. A comparison is made with the current literature to show that the proposed chirality CNT with small band-gap which makes faster switching Carbon Nanotube Field Effect Transistor (CNTFET).